Mobilizing Technology for Development : An Assessment of World Bank Group Preparedness - Independent Evaluation Group (World Bank, Washington, DC, 2021)
Disruptive and transformative technologies (DTT) have far-reaching implications for development. Traditional development models are being disrupted by the accelerating pace of technological change and the convergence of multiple technologies, among other things. Recognizing the implications of DTT for development, the World Bank Group adopted a new approach to DTT in 2018, later merging it with its 2019 DTT Mainstreaming approach, and further developing it through the 2020 Mainstreaming Digital and Disruptive Technologies (MDDT) Initiative. The Bank Group’s approach encompasses five DTT corporate priorities (country diagnostics, agile regulations, digital connectivity, digital government, and skills and capabilities for the new economy and the role of education), the Bali Fintech Agenda (financial technology and digital entrepreneurship), and sectoral and regional programs (for example, Digital Economy for Africa Moonshot/Accelerate and Middle East and North Africa Tech). The Bank Group aims to help clients harness the opportunities and mitigate the risks of DTT to accelerate progress toward achieving the twin goals of ending extreme poverty and boosting shared prosperity. This evaluation sought to answer the question, How well prepared is the Bank Group to help clients harness the opportunities and mitigate the risks posed by DTT?